2020
DOI: 10.1186/s13018-020-02067-w
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord-derived Wharton’s jelly for regenerative medicine applications in orthopedic surgery: a systematic review protocol

Abstract: Background Musculoskeletal injuries and conditions affect millions of individuals. These ailments are typically managed by immobilization, physiotherapy, or activity modification. Regenerative medicine has experienced tremendous growth in the past decades, especially in musculoskeletal medicine. Umbilical cord-derived Wharton’s jelly is an exciting new option for such therapies. Wharton’s jelly is a connective tissue located within the umbilical cord largely composed of mesenchymal stem cells and extracellular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The methodology of this systematic review followed the protocol that was previously published and registered on the international prospective register of systematic reviews (PROSPERO), registration number CRD42020182487 [43]. The various steps described in our published systematic review protocol were fully followed [41]; however, the search time range for published data was broadened from January 2010 to October 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of this systematic review followed the protocol that was previously published and registered on the international prospective register of systematic reviews (PROSPERO), registration number CRD42020182487 [43]. The various steps described in our published systematic review protocol were fully followed [41]; however, the search time range for published data was broadened from January 2010 to October 2021.…”
Section: Methodsmentioning
confidence: 99%
“…MSCs can be derived from various types of tissues from both allogenic and autogenic sources. These tissues include: adipose, bone marrow, placenta, amniotic fluid, umbilical cord, and umbilical cord-derived Wharton jelly [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that intraperitoneal administration of stem-cell-enriched umbilical cord blood cells (SCE-UCBCs) expanded from rat UCBCs attenuated HI brain injury in neonatal rats [ 17 ]. Wharton’s jelly, a gelatinous substance within the umbilical cord, is composed of extracellular matrix such as hyaluronic acid and CS [ 18 ]. CS and/or DS could conceivably be present in UCBCs.…”
Section: Introductionmentioning
confidence: 99%